The Role of Psychiatric Examination in the Forensic Medical Documentation of Repetitive Partner Violence Against Women - Günbeği, Meltem; Turla, Ahmet (The Bulletin of Legal Medicine, 2024)
Objective: This study aims to discuss the medicolegal significance of psychological examinations in the documentation of repetitive partner violence by evaluating the results of forensic reports prepared for such cases in detail.Methods: Case files those indictments were completed by the Public Prosecutor responsible for the Domestic Violence and Violence Against Women Bureaus in Samsun, were examined retrospectively between June 1, 2020, and December 1, 2020. The forensic reports of 141 women aged 18 and above who had previously reported violence by the same partner were selected and examined.Results: The psychiatric examination section of the reports revealed that psychiatric examination was not conducted in 74.5% (n=102) of cases, was recorded only as “normal or N” in 19% (n=26), and was recorded as no psychopathology was found in 2.9% (n=4). Psychiatric examinations were not performed in 72.4% (n=63) of cases with mild injuries that could be treated with simple medical interventions. In cases where the report stated no signs of physical violence, 72.2% (n=13) did not undergo a psychological examination.Conclusion: In medico-legal assessment of women subjected to repeated partner violence who represent a particular group with a high incidence of psychopathologies, appropriate examination conditions are often not provided, and psychiatric examinations are not conducted. A detailed psychological examination can more clearly establish the severity of injuries, and establishing the causality between trauma and psychological findings in the conclusion section of forensic reports will guide the judicial authorities in showing the presence of trauma in case of no physical finding.
Keywords: Repeated partner violence; forensic documentation; psychological examination